Peran Program MBKM Studi Independent Data Sains dalam Peningkatan Minat Mahasiswa Menjadi Data Analyst - Veronika Dita Pratiwi Putri Oktaviari; Trian Gigih Kuncoro (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aimed to analyz the impact of the MBKM (Merdeka Belajar Kampus Merdeka) program with an independent study of Data Science on increasing the interest of students at the University of Muhammadiyah Surakarta to become data analysts. The method used in this study is a descriptive qualitative method, which involves collecting data through in-depth interviews and observations of MBKM program participants. The results of the study indicate that the MBKM program, especially those related to the independent study of Data Science, has a positive impact on increasing student interest in the field of data analysis. Through experiential learning, such as internships and working on real projects, students gain technical skills that are relevant to industry needs as well as in-depth insights into the challenges and opportunities in the world of data science